Microsurgical Aspects of Middle Cerebral Artery Variations: Clinical and Anatomo-radiological Implications - Mustafa Eren Yüncü; Berra Bilgin; Yeliz Pekçevik; Ali Karadag; Necmettin Tanrıöver (Muğla Sıtkı Koçman Üniversitesi Tıp Dergisi, 2026)
The middle cerebral artery is the largest branch of the internal carotid artery and supplies extensive cortical and deep cerebral territories. Variations in its branching pattern are of considerable importance in microsurgical planning and may influence aneurysm development. This study aimed to evaluate the prevalence of middle cerebral artery variations, their microsurgical anatomy, and their relationship with anterior circulation aneurysms. Computed tomography angiography images of 500 patients were retrospectively reviewed to identify middle cerebral artery variations and anterior circulation aneurysms. Additionally, the microsurgical anatomy of the middle cerebral artery was demonstrated through dissections of two cadaveric heads. Descriptive statistical analyses were performed. Middle cerebral artery variations were identified in 62 patients (12.4%), with a total of 73 variations. The most frequent variants were trifurcation (n=35) and early cortical branch (n=24), followed by accessory middle cerebral artery (n=6), fenestration (n=6), and duplication (n=2). Eleven patients exhibited two concurrent variations. Anterior circulation aneurysms were detected in 118 patients, comprising 132 aneurysms in total. The most common locations were middle cerebral artery (n=53), posterior communicating artery (n=28), and anterior communicating artery (n=27). Fourteen patients harbored multiple anterior aneurysms. Aneurysms were present in 30.6% of patients with middle cerebral artery variations compared to 22.6% of those without variations. Among variation subtypes, trifurcation demonstrated the highest aneurysm rate (45.7%). Cadaveric dissections emphasized the surgical relevance of preserving early cortical branches and perforating arteries. Recognition of middle cerebral artery variations and their association with aneurysm distribution is essential for optimizing microsurgical strategy and improving neurovascular management.